Assessment of phytoplankton invasion risks in the ballast water of international ships in different growth conditions. Issue 4 (2nd October 2017) - Hyun, Bonggil; Baek, Seung Ho; Shin, Kyoungsoon; Choi, Keun-Hyung
Abstract : The possibility of successful invasion by phytoplankton assemblages in the ballast water of twelve international commercial ships was investigated. Various scenarios of port water dilution rates with a time delay for the exponential growth of the plankton were considered. Most of the phytoplankton in the ballast water samples originated in countries such as Japan and China, and diatoms dominated (>90% abundance) these phytoplankton communities. To assess their survival after discharge in seawater under various conditions, the phytoplankton were reintroduced into ballast water, pier-side water, and nutrient-enriched f/2 medium and incubated at various water temperatures and salinities for 2 weeks. The growth of the invading phytoplankton was influenced by the time delay for regrowth when introduced in the new seawater conditions. The results also suggest that once introduced by ballast water, the growth of a phytoplankton community may depend more on the nutrient levels and the water temperature and less on the salinity. Although we did not consider parameters such as competition with native species and predation, both high nutrient concentrations and water temperatures may significantly shorten the period before exponential growth occurs, which increases the invasion potential.